Prognostic value of the early lung ultrasound B-line score for postoperative pulmonary insufficiency in patients undergoing thoracic surgery: an observational study - Yipeng He; Xiaoxiao Xu; Chenhao Wang; Zhouquan Wu (European Journal of Medical Research, 2023)
Abstract Background Postoperative pulmonary insufficiency (PPI) is an important contributor to morbidity and mortality after thoracic surgery. Lung ultrasound is a reliable tool for assessing respiratory function. We sought to determine the clinical value of the early lung ultrasound B-line score for predicting changes in pulmonary function after thoracic surgery. Methods Eighty-nine patients undergoing elective lung surgery were included in this study. The B-line score was determined 30 min after removal of the endotracheal tube, and the PaO2/FiO2 ratio was recorded 30 min after extubation and on the third postoperative day. Patients were divided into normal (PaO2/FiO2 ≥ 300) and PPI (PaO2/FiO2 < 300) groups according to their PaO2/FiO2 ratios. A multivariate logistic regression model was used to identify independent predictors of postoperative pulmonary insufficiency. Receiver operating characteristic (ROC) analysis was performed for significantly correlated variables. Results Eighty-nine patients undergoing elective lung surgery were included in this study. We evaluated 69 patients in the normal group and 20 in the PPI group. Patients conforming to NYHA class 3 at administration were significantly more represented in the PPI group (5.8 and 55%; p < 0.001). B-line scores were significantly higher in the PPI group than in the normal group (16; IQR 13–21 vs. 7; IQR 5–10; p < 0.001). The B-line score was an independent risk factor (OR = 1.349 95% CI 1.154–1.578; p < 0.001), and its best cutoff value for predicting PPI was 12 (sensitivity: 77.5%; specificity: 66.7%). Conclusions Lung ultrasound B-line scores 30 min after extubation are effective in predicting early PPI in patients undergoing thoracic surgery. Trial registration This study was registered with the Chinese Clinical Trials Registry (ChiCTR2000040374).